Antibacterial and Antioxidant Activity of Endophytic Bacteria Isolated from Hibiscus tilaceus Leaves - Purbowatiningrum Ria Sarjono; Aulia Anggraeni; Afiina Putri Monita; Mukhammad Asy’ari; Ismiyarto Ismiyarto; Ngadiwiyana Ngadiwiyana; Nor Basid Adiwibawa Prasetya (Syarif Hidayatullah State Islamic University, 2022)
Antibacterial is a compound that inhibits or kills bacteria, especially infectious pathogenic bacteria. Antioxidants are compounds to inhibit the activity of free radicals in the body. The leaf extract of the waru plant (Hibiscus tiliaceus) is reported to have antibacterial, antioxidant, and anti-inflammatory activity. Bioactive compounds obtained from plants generally require a lot of plant availability and large areas for growth and take a long time. One solution to solve this problem is to isolateendophytic bacteria from plants. Endophytic bacteria are bacteria that live symbiotically in the host tissue so that they can produce the same bioactive compounds as the host. In the study, several stages were carried out, including isolation of endophytic bacteria from hibiscus leaves, gram-staining of bacteria, secondary metabolites production, antibacterial activity analysis by disk method,antioxidant activity analysis by DPPH free radical scavenger method, phytochemical screening, and identification of genotypic endophytic bacteria. Isolates of endophytic bacteria from Hibiscus tiliaceus leaves were obtained in cocci. They formed gram-positive bacteria with the closest relationship with Staphylococcus warneri strainAW 25 and Staphylococcus pasteuri strainATCC 51129. Endophytic bacteria from the Hibiscus tiliaceus leaves produce secondary metabolites containing alkaloids and saponins that can inhibit the growth of Staphylococcus aureus and Salmonella typhi and can be an antioxidant agent.